The Culprit of Bias for Paleointensity Estimation in the Shaw‐Type Protocol and an Innovative Calculation Method - Kaixian Qi; Shuhui Cai; Huafeng Qin; Yuhji Yamamoto; Chenglong Deng; Yongxin Pan; Xin Cheng; Hanning Wu; Rixiang Zhu (Geophysical Research Letters)
Abstract Paleointensity records are vital for understanding the Earth's evolution, but obtaining accurate paleointensity is a challenging task. The Shaw‐type method, a widely‐used paleointensity protocol, produces biased results occasionally despite strict selection criteria. By examining the relationships between paleointensities and rock magnetic parameters from a pseudo‐Tsunakawa‐Shaw experiment, we ascertain that changes in the ratio of thermal to anhysteretic remanent magnetization (R) are proportional to bias in paleointensity, especially prominent in samples with hundred‐nanometer‐scale magnetic grains, and thus proved to be the culprit for the bias. Furthermore, we develop a method exploiting the Linear regression of R with Diverse cut‐off coercivity intervals for estimating Shaw‐type paleointensities (LoRD‐Shaw). Combined with a curve fit technique for samples with “folding" phenomenon, the LoRD‐Shaw method yields high‐accuracy results in all tested samples, demonstrating its efficiency in mitigating paleointensity bias from thermal alteration. The new method will enhance acquisition of high‐precision paleointensities for constraining the geodynamo evolution.